DEMOGRAPHIC AND MIGRATION PROCESSES IN CENTRAL ASIA AND THEIR IMPACT ON UZBEK ETHNOGENESIS - Sattorov Nurbek Abdurazzokovych; Salimova Zebuniso Ilhom qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In this article, we examine the demographic and migration processes that shaped the ethnogenesis of the Uzbek people in Central Asia. Over several millennia, the region witnessed the migration of numerous groups, including Indo-Europeans, Iranians, Turks, and Mongols, all of whom contributed to the complex ethnic composition of the modern Uzbek population. The study examines how these migrations, combined with environmental, social, and political factors, influenced the genetic, linguistic, and cultural characteristics of the Uzbeks. Particular attention is paid to the role of nomadic and sedentary civilizations, as well as the influence of historical events such as the Mongol invasions, the rise of the Timurid Empire, and later Russian colonization. By analyzing historical sources, archaeological finds, and genetic studies, this article highlights the significant role of migration in shaping the identity and demographic landscape of the Uzbek people.